FGF10 promotes cardiac repair through a dual cellular mechanism increasing cardiomyocyte renewal and inhibiting fibrosis . Issue 12 (10th November 2021) - Hubert, Fabien; Payan, Sandy M; Pelce, Edeline; Bouchard, Laetitia; Sturny, Rachel; Lenfant, Nicolas; Mottola, Giovanna; Collart, Frédéric; Kelly, Robert G; Rochais, Francesca
Abstract: Aims: Promoting cardiomyocyte renewal represents a major therapeutic approach for heart regeneration and repair. Our study aims to investigate the relevance of FGF10 as a potential target for heart regeneration. Methods and results: Our results first reveal that Fgf10 levels are up-regulated in the injured ventricle after MI. Adult mice with reduced Fgf10 expression subjected to MI display impaired cardiomyocyte proliferation and enhanced cardiac fibrosis, leading to a worsened cardiac function and remodelling post-MI. In contrast, conditional Fgf10 overexpression post-MI revealed that, by enhancing cardiomyocyte proliferation and preventing scar-promoting myofibroblast activation, FGF10 preserves cardiac remodelling and function. Moreover, FGF10 activates major regenerative pathways including the regulation of Meis1 expression levels, the Hippo signalling pathway and a pro-glycolytic metabolic switch. Finally, we demonstrate that elevated FGF10 levels in failing human hearts correlate with reduced fibrosis and enhanced cardiomyocyte proliferation. Conclusions: Altogether, our study shows that FGF10 promotes cardiac regeneration and repair through two cellular mechanisms: elevating cardiomyocyte renewal and limiting fibrosis. This study thus identifies FGF10 as a clinically relevant target for heart regeneration and repair in man. Graphical Abstract: